Aspirin increases tolerance to high temperature in seeds of Raphanus sativus L. cvar Early Scarlet Globe - Takaki, M. [UNESP]; Rosim, R. E. [UNESP] (My University, 2000)
The incubation of seeds of Raphanus sativus L. cvar Early Scarlet Globe with 10 μM aspirin resulted in increase in the temperature range for germination. The analysis of percentage germination and germination rates indicated the increase in the optimum temperature from 21.4 to 26°C although at 32.6°C 80.8% of seeds germinated with aspirin and no germination in the control. The analysis of the kinetics of seed germination indicated that aspirin treatment resulted in germination by decreasing the enthalpy of activation of the process. The aspirin treatment also resulted in the synchronization of seed germination. On the base of our results we propose aspirin application in practice to increase the tolerance to high temperature and to synchronize seed germination at least in Raphanus sativus L. cvar early scarlet globe.